Two faces of Corporate Responsibility. Relationships between Celsia and the community of El Caney during the building of Hidromontañitas Hydroelectric Power Station - Preciados Hoyos, Ángela (2017)
This paper gives an account of the most relevant aspects of the management of corporate responsibility and of the relations between the company Celsia and a group of inhabitants of El Caney in Santa Rosa de Osos, Colombia, during the construction of the Hidromontañitas plant. The methodology followed consisted of an in-depth interview with Celsia’s communications professional and the development of a focus group with members of the community. The information obtained has been contrasted taking into account what companies and community understand about what is corporate responsibility, as well as aspects associated with the relationship process, in terms of community participation and the fulfillment of the commitments agreed with its expectations.